"UNNATURAL" DISASTERS AND INJUSTICE IN THE INDIAN RISKSCAPE: UNLEASHING YOUTH POTENTIAL. Issue 4 (7th August 2020) - Calabrese, John
Abstract : The vulnerabilities that turn natural hazards such as hurricanes and earthquakes into disasters are rooted in inequality. The overarching aim of this article is to shed light on the nexus between social justice principles and the mitigation of disaster impacts. The article uses 'disaster justice' – an offshoot of 'environmental justice' – as a conceptual lens to help enrich understanding of the differential impacts of disasters upon communities and to craft more inclusive policies and programmes. In India, among the world's most disaster-prone countries, as elsewhere, there is growing recognition that children and youth, who assume a disproportionate share of the burden created by disasters, are an underutilized demographic force multipliers for disaster risk reduction. The country's multi-hazard risk and vulnerability profile has led Indian non-governmental organisations (NGOs) not just to provide post-disaster relief but increasingly to integrate into their work programs designed to unleash the potential of young people to develop the resilience of their communities.